Enhancement of efficiency of water electrolysis for hydrogen production - Mazloomi, Seyedkaveh (2013)
In this thesis, after analyzing the properties of hydrogen in analogy to a number of common fuels, its productions methods and advantages of water electrolysis are introduced briefly. The frequency response of a water electrolysis cell is analyzed in order to examine the possibilities of reaching higher production efficiencies in other methods of power application than steady DC mode. Conductance of such cells was observed to reach a maximum value at a certain frequency depending on the physical cell characteristics. As a result, a series of experiments were continued in order to examine the possibility of enhancing the process efficiency. Laboratory tests were performed on a cell in different voltages ranging between 2 V and 10 V, frequencies ranging between DC and 20 MHz and duty cycles varying in the range of 10% to 100%. The efficiency value was recorded for each case and the results were compared with those of DC mode. The gathered data shows water electrolysis process will be more efficient when the power is applied to the cell in the form of pulses. According to the experimental results, an efficiency enhancement of up to 14% can be achieved by applying short pulses to the system instead of a DC voltage. The result of the latter is prevention of the formation of retarding phenomena such as electrical double layers and diffusion layer in the vicinity of the electrodes. However, the production rate decreases in pulsating power application since the total amount of energy application to an electrolytic bath is remarkably reduced in pulsating voltage application mode. In other words, the time requirement of producing the same amount of hydrogen can be longer as much as near 3 times of that of low efficiency process.